Individual differences in the amount and timing of salivary melatonin secretion. - Helen J Burgess; Louis F Fogg (PLoS ONE)
The aim of this study was to examine individual differences in a large sample of complete melatonin profiles not suppressed by light and search for possible associations between the amount and timing of melatonin secretion and a multitude of lifestyle variables. The melatonin profiles were derived from saliva samples collected every 30 minutes in dim light from 85 healthy women and 85 healthy men aged 18-45 years. There was a large individual variability in the amount of melatonin secreted with peak values ranging from 2 to 84 pg/ml. The onset of melatonin secretion ranged from 18:13 to 00:26 hours. The use of hormonal birth control, reduced levels of employment, a smaller number of days on a fixed sleep schedule, increased day length and lower weight were associated with an increased amplitude of melatonin secretion. The use of hormonal birth control, contact lenses, a younger age, and lower ratings of mania and paranoia were associated with a longer duration of melatonin secretion. An earlier occurrence of the onset of melatonin secretion was associated with an earlier wake time, more morningness and the absence of a bed partner. Lifestyle and behavioral variables were only able to explain about 15% of the individual variability in the amount of melatonin secretion, which is likely because of a substantial genetic influence on the levels of melatonin secretion.